AAV Delivery of shRNA Against TRPC6 in Mouse Hippocampus Impairs Cognitive Function - Xie, Ruxin; Wang, Zhongke; Liu, Tianyao; Xiao, Rui; Lv, Keyi; Wu, Chuan; Luo, Yi; Cai, Yun; Fan, Xiaotang (Frontiers in Cell and Developmental Biology, 2021)
Transient Receptor Potential Canonical 6 (TRPC6) has been suggested to be involved in synapse function and contribute to hippocampal-dependent cognitive processes. Gene silencing of TRPC6 was performed by injecting adeno-associated virus (AAV) expressing TRPC6-specific shRNA (shRNA-TRPC6) into the DG. Spatial learning, working memory and social recognition memory were impaired in the shRNA-TRPC6 treated animals compared to control after four weeks. In addition, gene ontology analysis of RNA-sequencing revealed that viral intervention of TRPC6 expression in DG resulted in the enrichment of the process of synaptic transmission and cellular compartment of synaptic structure. Furthermore, the shRNA-TRPC6 treatment reduced dendritic spines of DG granule neurons, in terms of spine loss, the thin and mushroom types predominated. Accompanying the spine loss, the level of PSD95 in the hippocampus was decreased in the shRNA-TRPC6 treated animals. Taken together, our results suggest that that knocking down TRPC6 in the DG have a disadvantageous effect on cognitive processes.